Scheduling Regular Classrooms using Heuristic Genetic and Tabu Search Algorithms - Fauziah, N F; Putra, Y H (IOP conference series. Materials Science and Engineering, 2018)
The purpose of this study was to scheduling regular classrooms using heuristic genetic and tabu search algorithm. Scheduling in the university environment - related subject is very important, as it pertains to the number of students, limited spaces, lecturer limited, as well as the time available. With all these parameters should get the best solution in terms of timetable by observing any limitations. Heuristic algorithms of optimization strategy is one that can be used in a search schedule. In practice heuristic algorithms in scheduling using genetic algorithm and tabu search. Genetic engineering is used to find the value of a high probability, while tabu search to optimize the number of searches and maintaining the high value that is already generated. The results of this research, namely scheduling using genetic and tabu search algorithm for schedule a number of students who are scheduled, as well as a fitness value with a high number of iterations that bit, so make scheduling with quality better and less time.